Springs ecosystems: vulnerable ecological islands where environmental conditions, life history traits, and human disturbance facilitate non-native plant invasions - Nielson, Kayleigh G.; Gill, Karen M.; Springer, Abraham E.; Ledbetter, Jeri D.; Stevens, Lawrence E.; Rood, Stewart B. (Biological invasions, 2019)
Ecosystem invasion by non-native plants depends on plant life history characteristics that influence the species’ invasiveness, as well as environmental factors that determine site invasibility. Small, insular ecosystems are thought be especially vulnerable to invasion but evidence for this pattern has been mixed. Freshwater springs form island-like ecosystems, allowing for a test of this proposal. Here, we investigated the effects of physical environmental factors, human disturbance, and plant life history traits on the occurrence of native and non-native plant species at 55 springs across different biomes in Alberta, Canada. A total of 526 plants were identified, 12.5% of which were non-native. Among these, species richness and abundance were greater at springs within biomes subject to increased land use intensity, especially livestock grazing, as compared to springs in parks and protected areas with limited land use. Subsequently, springs with higher human impact supported greater richness ( r 2 = 0.13) and abundance ( r 2 = 0.31) of non-native species, while native species abundance declined with increasing human impact ( r 2 = 0.14). Common native and non-native plant taxa exhibited life history traits that confer greater tolerance to human disturbance, such as that arising from livestock production that can disperse propagules, including clonal capacity and physical and chemical herbivory defenses. Our results indicated that springs ecosystems with greater human disturbance were more vulnerable to invasion by non-native plants, and this can reduce plant biodiversity and the ecological services provided by these distinctive, insular ecosystems.